Mermaids [videorecording (DVD)] - Roberts, June; Lloyd, Lauren; Nicita, Wally; Palmer, Patrick; Cher, 1946-; Benjamin, Richard, 1938-; Hoskins, Bob; Ryder, Winona, 1971-; Schoeffling, Michael; Ricci, Christina; Atherton, Howard; Cambas, Jacqueline; et al. (MGM DVD., 2001)
Charlotte is an adolescent girl torn between her blossoming passion for a handsome caretaker and her desire to be a nun (a tough calling for a girl who's Jewish). Complicating her already precarious teen angst is a little sister, an obsessive swimmer, and her mother, a non-traditional, sexy, flamboyantly eccentric woman who relocates them to a new town every time she causes a hint of scandal--which is often.